Penguatan Akuntabilitas Laporan Keuangan Konsolidasi Sebagai Strategi Berkelanjutan BUMDes Kalongan Mandiri Jaya - Gunawati, Iva Sofi; Mahmud, Amir; Susilowati, Nurdian (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Strengthening consolidated financial reporting is a key factor in supporting the business sustainability of Village-Owned Enterprises (BUMDes). The Kalongan Mandiri Jaya BUMDes faces various challenges in managing its financial reports, such as limited accounting knowledge, an unintegrated reporting system, and minimal transparency and accountability. To address these challenges, a program to strengthen consolidated financial reporting is proposed through several strategic solutions, including accounting training for BUMDes managers, the implementation of an integrated financial reporting system, and strengthening internal controls to enhance transparency and accountability. The target outcomes of this program include improving accounting understanding for BUMDes managers, implementing consolidated financial reports, and improving the transparency and accountability system. The results of the research and community service programs demonstrate that the Kalongan Mandiri Jaya BUMDes is able to strengthen its financial governance, increase competitiveness, and ensure long-term business sustainability. Overall, this program received positive feedback from BUMDes managers. They believe the mentoring provided has opened new insights into the importance of accountability and transparency in fund management. Furthermore, this activity has also been proven to strengthen the capacity of BUMDes in compiling reports to external parties, including village governments, business partners, and financing institutions.